Proses Pembuatan Peraturan Daerah Terkait Pendidikan di Kota Bukittinggi - Zahra Putri Salsabila (CV. ITTC INDONESIA, 2025)
The establishment of Regional Regulations on Education (PERDA) in Bukittinggi City plays a vital role in ensuring quality, accessibility, and sustainability in education. This study examines the process of developing these regulations and highlights the stages of planning, detailing, discussion, ratification, and implementation. This study pursues a qualitative approach and analyzes the roles of the Regional Representative Council (DPRD), local governments, and other stakeholders in the design of education policies. The results show that regulatory frameworks are available, such as Law No. 12 of 2011 and Presidential Regulation 87 of 201, but there are several challenges. These include limited public participation, difficulties in aligning local regulations with political dynamics that influence national politics and legislative procedures. In addition, financial constraints and the availability of qualified legal writers will affect the effectiveness of PERDA implementation. To enhance the process, this study suggests greater transparency, increased stakeholder involvement, and improved coordination between local and national policy frameworks. Strengthening public engagement and ensuring sufficient budget allocation for education policies are also essential. By adopting a more inclusive and systematic approach, Bukittinggi City can develop regional regulations that effectively address educational needs and support sustainable development.